Current concepts on the relationship between abscisic acid and leaf water stress - Passos, Leônidas P. (Pesquisa Agropecuaria Brasileira, 2014)
A review of the available information on the relationship between ABA (abscisic acid) and leaf water stress is presented. Major subjects focused on are: leaf ABA content and water stress, possible mechanisms of ABA-induced stomatal closure, ABA effects as related to CO2 and other plant hormones, ABA and proline accumulation, and ABA as related to the "after-effect" of water stress. Remarkable results and some contradictory data are commented on briefly. Finally, the extension of present knowledge is analyzed and suggestions for further work are made.